PEMBUATAN BUSANA PESTA MENGGUNAKAN KOMBINASI KAIN SHIBORI DENGAN VARIASI SULAMAN PITA JEPANG - Arina Haq; Aldhis Safitry (Garina, 2021)
Shibori fabrics is one of the kind materials which has its own circlenes especially in its uniqe and ethnic design, it's light but it looks elegant.This research will innovate to shibori fabrics which will be cultivated become party clothing, to beautify party clothing performance which is made, the writter applied one of the ornaments that is "ribbon needlework".the writter took the title the production of party clothing by using the combination of shibori fabrics and Japanese embroidery variations because he wanted to know a sartorial costume technique that combines the sheboris with a embroidered Japanese ribbon. It USES methods: observation, literature and documentation. The result of the completion of the dressmaking process, the combination of shibori fabrics with a variety of embroidery bands, is that shibori cloth can be used as a combination for the dress of the party, but some important things need to be noted, such as the selection of a shibori cloth, a motif of the shibori colors. Also, the combination of other fabrics is crucial to supporting the shibori cloth to give a more extravagant appearance, while the application of the bow on the wedding dress provides an interesting result, but there are some things to consider in applying for the embroidery of the ribbon, such as, the embroidery of the ribbon must fit and not look so full, the design of the ribbon's embroidery should fit the cloth that is filled, And the selection of tape colors as well as the tape size to be applied.